2018
DOI: 10.1101/gr.220780.117
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome evidence reveals enhanced autophagy-lysosomal function in centenarians

Abstract: Centenarians (CENs) are excellent subjects to study the mechanisms of human longevity and healthy aging. Here, we analyzed the transcriptomes of 76 centenarians, 54 centenarian-children, and 41 spouses of centenarian-children by RNA sequencing and found that, among the significantly differentially expressed genes (SDEGs) exhibited by CENs, the autophagy-lysosomal pathway is significantly up-regulated. Overexpression of several genes from this pathway, CTSB, ATP6V0C, ATG4D, and WIPI1, could promote autophagy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 64 publications
3
46
0
Order By: Relevance
“…In support of this idea, healthy centenarians have been shown to have significantly higher levels of circulating beclin-1 compared to both young patients who have experienced an acute myocardial infarction and healthy young controls (Emanuele et al, 2014). This observation has been independently confirmed in a recent study that also showed a general increase in the expression of genes in the autophagy-lysosomal pathway in centenarians (Xiao et al, 2018).…”
Section: Insulin/igf-1 Signaling (Iis)supporting
confidence: 62%
“…In support of this idea, healthy centenarians have been shown to have significantly higher levels of circulating beclin-1 compared to both young patients who have experienced an acute myocardial infarction and healthy young controls (Emanuele et al, 2014). This observation has been independently confirmed in a recent study that also showed a general increase in the expression of genes in the autophagy-lysosomal pathway in centenarians (Xiao et al, 2018).…”
Section: Insulin/igf-1 Signaling (Iis)supporting
confidence: 62%
“…368 On the other hand, transcriptome evidence has revealed enhanced autophagy-lysosome function in centenarians. 369 PPARA-mediated autophagy can reduce AD-like pathology and cognitive decline. 370 These results suggest that autophagy is a potential therapeutic target for AD.…”
Section: Opinionsmentioning
confidence: 99%
“…With the development of genomic research, transcriptomics is one of the most widely used technologies ( Costa et al., 2010 ) that has been already used in studies of porcine growth ( Adapala and Kim, 2017 ), chicken skeletal muscle development ( Li et al., 2012b ), screening of sperm motility regulators ( Sun et al., 2019 ), human aging ( Xiao et al., 2018 ), poultry disease screening ( Matulova et al., 2012 ), and general genetic diversity ( Li et al., 2012a ). In poultry, most transcriptome studies focus on growth traits ( Allais et al., 2018 ) and meat quality ( Teng et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%